Income and policy choices: Evidence from parliamentary decisions and referenda - David Stadelmann; Marco Portmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2014)
We analyze political representation of preferences of different income groups by matching referendum outcomes for low, middle, and high-income voters with individual legislators' decisions on identical policy proposals. Results indicate that legislators more closely represent preferences of rich voters than preferences of middle-income and poor voters, and legislators are more responsive towards the rich. Preferences of low, middle, and high-income voters are, however, correlated. Representation of income groups varies according to legislators' party affiliations.
Keywords: D72; H70; 330; Income; policy decisions; representation; voting; referenda; political behavior